Identification of Key Genes and Pathways in Persistent Hyperplastic Primary Vitreous of the Eye Using Bioinformatic Analysis - Thomas, Derin M.; Kannabiran, Chitra; Balasubramanian, D. (Frontiers in Medicine, 2021)
Background: The failure of the embryonic hyaloid vascular system to regress naturally causes persistent hyperplastic primary vitreous (PHPV), a congenital eye disease. PHPVs molecular pathway, candidate genes, and drug targets are unknown. The current paper describes a comprehensive analysis using bioinformatics to identify the key genes and molecular pathways associated with PHPV, and to evaluate potential therapeutic agents for disease management. Methods: The genes associated with PHPV were identified using the pubmed2ensembl text mining platform. GeneCodis was employed to evaluate the Gene Ontology (GO) biological process terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Search Tool for the Retrieval of Interacting Genes (STRING) constructed a protein-protein interaction (PPI) network from the text mining genes (TMGs) in Cytoscape. The significant modules were clustered using Molecular Complex Detection (MCODE), and the GO and KEGG analysis for the hub genes were analyzed with the Database of Annotation, Visualization and Integrated Discovery (DAVID) tool. ClueGO, CluePedia, and ShinyGo were used to illustrate the functions and pathways of the clustered hub genes in a significant module. The Drug-Gene Interaction database (DGIdb) was used to evaluate drug–gene interactions of the hub genes to identify potential PHPV drug candidates. Results: A total of 50 genes associated with PHPV were identified. Overall, 35 enriched GO terms and 15 KEGG pathways were discovered by the gene functional enrichment analysis. Two gene modules were obtained from the PPI network constructed with 31 nodes with 42 edges using MCODE. We selected 14 hub genes as core candidate genes: TP53, VEGFA, SMAD2, CDKN2A, FOXC, FZD4, LRP5, KDR, FZD5, PAX6, MYCN, NDP, PITX2, and PAX2, primarily associated with camera-type eye morphogenesis, pancreatic cancer, the apoptotic process involved in morphogenesis, and the VEGF receptor signaling pathway. We discovered that 26 Food and Drug Administration (FDA)-approved drugs could target 7 of the 14 hub genes. Conclusions: In conclusion, the results revealed a total of 14 potential genes, 4 major pathways, 7 drug gene targets, and 26 candidate drugs that could provide the basis of novel targeted therapies for targeted treatment and management of PHPV.